Flypaper Effect in North Maluku: Investigating the Role of Local Own-Source Revenue, General Allocation Fund, Special Allocation Fund, And Revenue Sharing Fund on Regional Expenditure - Muhammad Hasnin; Mohammad Kotib; Nurdin I Muhammad (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to analyze the occurrence of the Flypaper Effect on regional spending in the regencies/cities of North Maluku Province using four main variables: Local Own-Source Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH). The Flypaper Effect refers to a phenomenon where transfers from the central government, such as DAU, significantly impact regional spending more than local own-source revenue. This study employs a quantitative method with a Fixed Effect regression model. The data used are panel data from 10 regencies/cities in North Maluku Province over the 2017-2022 period. The results show that both DAU and PAD significantly influence regional spending. However, based on Wulansari's (2015) criteria, since PAD is also significant and DAU's influence is not dominantly greater than PAD, the Flypaper Effect does not occur in the regencies/cities of North Maluku. Furthermore, DAK does not significantly affect regional spending, while DBH is close to the significance threshold. These findings suggest that, while DAU and PAD are both significant, local governments still have the potential to enhance fiscal independence by optimizing PAD.